Dual Fixation of Calcaneal Tuberosity Avulsion with Concomitant Achilles Tendon Rupture: A Novel Hybrid Technique. (5th March 2017) - Prabhakar, Gautham; Kusnezov, Nicholas; Rensing, Nicholas; Abdelgawad, Amr
Abstract : Fracture of the calcaneal tuberosity with a concomitant Achilles tendon rupture presents a difficult challenge for the treating surgeon. The ultimate goal of treatment is to restore function of both the gastrocnemius-soleus complex and the Achilles tendon. This particular subset of fractures occurs often in diabetics and elderly patients with osteoporosis making fixation of the displaced fragment rather complex. If the Achilles tendon disruption is only discovered later once the fracture is healed, subsequent management is difficult with surgical treatment being more morbid. While this is a rare injury, the consequences of a missed chronic Achilles tendon disruption are severe with significant dysfunction. It is therefore important to have a high index of suspicion for concomitant injury and to be prepared for dual fixation. We present a novel hybrid surgical fixation technique, which may be used in this instance.